Highly efficient double side mechanically textured novel silicon solar cell concepts - Terheiden, Barbara; Fath, Peter (My University, 2003)
Silicon solar cell concepts based on double side mechanical V-texturing were developed and investigated. In the case of the MECOR (MEchanically CORrugated) solar cell concept, the V-grooves run parallel on the front and rear sides while the BOSS (BOth Sides Perpendicularly Structured) solar cell concept is based on perpendicular V-grooves on the front and rear sides. The solar cell contacting was mainly done using the SAP&SAFE (Shallow Angle Photolithography & Shallow Angle Finger Evaporation) concept which was specifically developed for V-textured surfaces. The highest efficiency achieved for MECOR solar cells was 18.5%. For BOSS solar cells an efficiency of 19.3% was demonstrated. Optical simulations of different geometric cell structures were done.
Keywords: 530